Biblija, slovenski jezik in slovenska literatura - Snoj, Vid (Primerjalna književnost, 2005)
Narrating the story of the Bible, the Slovene language and Slovene literature,the present paper follows of four threads in the complicated weave of this story: the Slovene translation of the Bible in 16th century, the emergence of Slovene literature in the second half of 18th century and then, within the framework of Slovene literature, the secularisation of the Bible in Preseren's high Romantic poetry, and the formation of the paradigm of yearning with the aid of the Bible in Cankar's prose almost a century later.
Keywords: Biblija; Cankar, Ivan, 1876-1918; Prešeren, France, 1800-1849; prevodi v slovenščino; Slovene literature; slovenska književnost; svetopisemski jezik; svetopisemski motivi